Caracterização do abastecimento de água no município de Alto Santo-Ce - Santos, Daniely Palony Targino dos (Universidade Federal Rural do Semi-Árido, 2018)
Water is an indispensable natural resource for life, it is essential for the development of practically all the activities carried out by man on Earth; however it is a limited resource and its distribution is uneven. The objective of this study is to perform the diagnosis of water supply in the municipality of Alto Santo - CE. The research was carried out with on-site visits to the Water Supply System (SAA) of the municipality. Analyzes of water samples from the CAGECE and City Hall sources were carried out through physicochemical and microbiological tests in the CAGECE and Jaguaribana Regional University laboratories, respectively, following the standard procedures established by Ministry of Health 508 and pressure monitoring carried out in the distribution network with the installation of a datalogger. Data were collected from the residents, through interviews, being applied in a finite population, with a sample of 100 residences. By means of a diagnosis, it is concluded that the water supply in the municipality of Alto Santo presents several problems related to quantity and quality, in order to not meet current demand. CAGECE has not been able to universalize the service, and most of the users have been creating alternative systems of water supply (well drilling and car pipes). The analyzes of the water quality distributed by CAGECE presented results outside the potability standards required by ordinance no. 2,914 / 2011; the results of physical-chemical reports presented nonconformity indexes; and the results of the bacteriological analyzes of the samples collected at the exit of the treatment and the SAA distribution network showed non-compliance with the presence of total coliforms (NMP / 100ml) in one of the samples. The water distributed by the municipal government does not go through any type of treatment: according to research, 100% of the samples were found to be in disagreement with the current legislation, regarding turbidity, apparent color, PH and residual chlorine; 100% of the analyzes carried out on PT 01 samples showed noncompliance for total coliforms and 100% of the analyzes performed on PT 02 samples showed compliance with the standards established by Ordinance MS 2,914 / 11.
Monografia
Keywords: Água; Sistema de abastecimento; Alto Santo; Ceará; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA